The effect of Physalis Angulata l. (Ciplukan) fruit extract on preeclamptic trophoblast cell cultures on TGF-β and TNF-α levels - Sie Ernawati; I Gusti Ayu Ratih Parmita; Harry Kurniawan Gondo; Kuntaman Kuntaman; Nisye Pricilya Apriani Paembonan (Malahayati International Journal of Nursing and Health Science, 2026)
Background: Preeclampsia is a pregnancy complication characterized by hypertension, proteinuria, and dysfunction of other organs, which can endanger both the mother and the fetus. Due to its complex pathophysiology involving inflammatory and immunological processes, exploration of alternative therapies with anti-inflammatory potential is needed. Physalis angulata L. (ciplukan) is known to contain bioactive compounds that may modulate inflammatory mediators. Purpose: To evaluate the effectiveness of parental holding as a non-pharmacological intervention in reducing pain and anxiety responses in children undergoing invasive hospital procedures, particularly among critically ill pediatric patients Method: This study evaluated the effects of ciplukan fruit extract on TGF-β and TNF-α levels in preeclamptic trophoblast cell cultures. Trophoblast cells were isolated from placentas of patients with preeclampsia and treated with various doses of ciplukan fruit extract. Levels of TGF-β and TNF-α were measured using the ELISA method Results: The implementation of parental holding during invasive procedures was associated with a reduction in children’s pain responses and anxiety levels. Children who received parental holding showed calmer behavior, reduced distress, and improved cooperation during procedures such as IV insertion and injections compared to those who did not receive the intervention. Conclusion: Parental holding is an effective non-pharmacological intervention for reducing pain and anxiety in children undergoing invasive hospital procedures. This approach can be safely applied, particularly in critically ill children, to improve comfort and support family-centered care in pediatric settings.